White Spot Syndrome Virus Triggers a Glycolytic Pathway in Shrimp Immune Cells (Hemocytes) to Benefit Its Replication - Ng, Yen Siong; Lee, Der-Yen; Liu, Chun-Hung; Tung, Cheng-Yi; He, Shu-Ting; Wang, Han-Ching (Frontiers in Immunology, 2022)
White spot syndrome virus (WSSV) is the causative agent of a shrimp disease that inflicts in huge economic losses in shrimp-farming industry. WSSV triggers aerobic glycolysis in shrimp immune cells (hemocytes), but how this virus regulates glycolytic enzymes or pathway is yet to be characterized. Therefore, mRNA levels and activity of four important glycolytic enzymes, Hexokinase (HK), Phosphofructokinase (PFK), Pyruvate kinase (PK), and Lactate dehydrogenase (LDH), were measured in WSSV-infected shrimp hemocytes. Gene expression of HK and PFK, but not LDH or PK, was increased at the viral genome replication stage (12 hpi); furthermore, activity of these enzymes, except HK, was concurrently increased. However, there was no increased enzyme activity at the viral late stage (24 hpi). In vivo dsRNA silencing and glycolysis disruption by 2-DG further confirmed the role of glycolysis in virus replication. Based on tracing studies using stable isotope labeled glucose, glycolysis was activated at the viral genome replication stage, but not at the viral late stage. This study demonstrated that WSSV enhanced glycolysis by activating glycolytic enzyme at the viral genome replication stage, providing energy and biomolecules for virus replication.